Gaya Angkat dan Perbedaan Tekanan di Dalam dan Luar Apollo Koran - Riani Eka Fitri; Irlian Nurmaniah; Irzaman Irzaman (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
The square paper Apollos were made from papers and needles with average area 0.005 m2 and 0.00146 kg total mass. It could fly if the burning occupied on the four angel corner of Apollos, this phenomena was due to outside pressure was higher than inside’s. The obtained result of lift force and pressure change of the ten paper Apollos by using kinematic of accelerated motion and Second Newton’s Law were about 0.15 - 0.17 N and 2-3 Pa on 1,2,and 3 meters height. Key words: Paper Apollo, Law of Kinematic and Second Newton, Lift Force, Pressure, Position.